In Situ Investigation of Leaf Water Status by Portable Unilateral Nuclear Magnetic Resonance - Capitani, Donatella; Brilli, Federico; Mannina, Luisa; Proietti, Noemi; Loreto, Francesco (PLANT PHYSIOLOGY, 2009)
A portable unilateral nuclear magnetic resonance (NMR) instrument was used to detect in field conditions the water status of leaves of herbaceous crops (Zea mays, Phaseolus vulgaris), mesophyllous trees (Populus nigra), and natural Mediterranean vegetation characterized by water-spending shrubs (Cistus incanus) and water-saving sclerophyllous trees (Quercus ilex). A good relationship was observed between NMR signal, leaf relative water content, and leaf transpiration in herbaceous leaves undergoing fast dehydration or slowly developing a drought stress. A relationship was also observed between NMR signal and water potential of Populus leaves during the development of a water stress and when leaves recovered from the stress. In the natural vegetation, the relationship between NMR signal and water status was found in Cistus, the species characterized by high transpiration rates, when measured during a drought stress period and after a rainfall. In the case of the sclerophyllous Quercus, the NMR signal, the relative water content, and the transpiration rate did not change at different leaf water status, possibly because a large amount of water is compartmentalized in cellular structures and macromolecules. The good association between NMR signal and relative water content was lost in leaves exposed for 24 h to dehydration or to an osmotic stress caused by polyethylene glycol feeding. At this time, the transverse relaxation time became longer than in leaves maintained under optimal water conditions, and two indicators of membrane damage, the ion leakage and the emission of products of membrane lipoxygenation \{[\}(Z)-3-hexenal, (Z)-3-hexenol, and (E)-2-hexenol], increased. These results taken all together give information on the physiological state of a leaf under a developing stress and show the usefulness of the NMR instrumentation for screening vegetation health and fitness in natural and cultivated conditions. It is concluded that the portable unilateral NMR instrument may be usefully employed in field conditions to monitor nondestructively the water status of plants and to assist agricultural practices, such as irrigation scheduling, to minimize stomatal closure and the consequent limitation to plant production.
Keywords: Drought stress; Mediterranean vegetation; natural vegetation; nuclear magnetic resonance; Quercus ilex

In Situ Investigation of Leaf Water Status by Portable Unilateral Nuclear Magnetic Resonance - Capitani, Donatella; Brilli, Federico; Mannina, Luisa; Proietti, Noemi; Loreto, Francesco (PLANT PHYSIOLOGY, 2009)
A portable unilateral nuclear magnetic resonance (NMR) instrument was used to detect in field conditions the water status of leaves of herbaceous crops (Zea mays, Phaseolus vulgaris), mesophyllous trees (Populus nigra), and natural Mediterranean vegetation characterized by water-spending shrubs (Cistus incanus) and water-saving sclerophyllous trees (Quercus ilex). A good relationship was observed between NMR signal, leaf relative water content, and leaf transpiration in herbaceous leaves undergoing fast dehydration or slowly developing a drought stress. A relationship was also observed between NMR signal and water potential of Populus leaves during the development of a water stress and when leaves recovered from the stress. In the natural vegetation, the relationship between NMR signal and water status was found in Cistus, the species characterized by high transpiration rates, when measured during a drought stress period and after a rainfall. In the case of the sclerophyllous Quercus, the NMR signal, the relative water content, and the transpiration rate did not change at different leaf water status, possibly because a large amount of water is compartmentalized in cellular structures and macromolecules. The good association between NMR signal and relative water content was lost in leaves exposed for 24 h to dehydration or to an osmotic stress caused by polyethylene glycol feeding. At this time, the transverse relaxation time became longer than in leaves maintained under optimal water conditions, and two indicators of membrane damage, the ion leakage and the emission of products of membrane lipoxygenation \{[\}(Z)-3-hexenal, (Z)-3-hexenol, and (E)-2-hexenol], increased. These results taken all together give information on the physiological state of a leaf under a developing stress and show the usefulness of the NMR instrumentation for screening vegetation health and fitness in natural and cultivated conditions. It is concluded that the portable unilateral NMR instrument may be usefully employed in field conditions to monitor nondestructively the water status of plants and to assist agricultural practices, such as irrigation scheduling, to minimize stomatal closure and the consequent limitation to plant production.
The following values have no corresponding Zotero field: pub-location: 15501 MONONA DRIVE, ROCKVILLE, MD 20855 USA publisher: AMER SOC PLANT BIOLOGISTS
Keywords: Drought stress; Mediterranean vegetation; natural vegetation; nuclear magnetic resonance; Quercus ilex